Analysis of the Effect of The Addition of LED Lights on Squid Fishing Gear (Squid Jigger) On Catches in Karimunjawa, Jepara, Central Java - Irawan, Willy Puspa (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2023)
Squid fishing line (Squid Jigger) is one of the fishing gear that is widely used by fishermen in Karimunjawa, Jepara. Squid fishing gear has long been known and operated with lights to attract the attention of squid that are installed in the fishing fleet, over time the squid fishing fleet has increased every year which indirectly increases competition in squid fishing activities. So it is necessary to add a light attractor in the form of a flashing LED light mounted on the main line of the squid fishing line. The purpose of this study was to analyze the effect of adding LED lights to squid fishing gear on catches and the effectiveness of fishing gear. The research method used is experimental fishing with 2 test variables, namely the use of blue and green LED lights with 16 repetitions in 2 fishing operations trips. Based on the research that has been done, the results show that the addition of LED lights has a significant effect on the catch of squid fishing gear with blue LED lights as the most effective in fishing operations because it gets the most catches, namely 7 fish and gets the fastest response from the target fish , namely 43 minutes from the first repetition.